Science-Fiction Movies and Religion - Natalie Fritz; Daria Pezzoli-Olgiati; Bina Nir; James Lorenz; Joel Mayward; Kerry San Chirico; Elie Yazbek; Kathrin Trattner; René Erwich; Hannah Griese; Stefanie Knauss; Marie-Therese Mäder (Schüren Verlag, 2021)
In science fiction films, we explore remote universes and use yet unknown technologies – the world as we know it is left behind. But although the technical devices in these films are impressive and the science advances in huge steps, the protagonists still search for a superior entity, for the main creator, for a god, for a lost paradise… The human quest for knowledge and for the unknown does not end, and the questions remain the same: What is humankind in relation to the undiscovered universe? Are we, in the near future, able to unravel all the mysteries that have always been tantalizing scientists and religious seekers? What ethical challenges might this progress bring? Will we become gods, “creating” humans by writing genetic codes using synthetic biology? The Interactions between science fiction and religion are manyfold and amazing …